Transitioning from epicutaneous to oral peanut immunotherapy - Wong, Lauren; Kost, Laurie; Anderson, Brent; Long, Andrew; Sindher, Sayantani B.; Chinthrajah, R. Sharon; Collins, William J. (Frontiers in Allergy, 2023)
Introduction Epicutaneous immunotherapy (EPIT) has been tested in clinical trials for children with peanut allergy (PA) for its safety and efficacy in inducing desensitization. Aside from peanut avoidance and symptom management, oral immunotherapy (OIT) is another option for PA patients. However, OIT can be associated with adverse events and pose safety concerns to children and their caregivers. Methods This study assessed 27 children who successfully completed a peanut EPIT trial. 18 of them transitioned to peanut OIT with starting doses ranging from 10–600 mg of peanut protein. Our aim was to learn more about the EPIT to OIT experience through descriptive survey responses and to gather information that may support the sequential use of the two immunotherapies for safe and positive outcomes that may not be achieved by either alone. Results Overall, children and their caregivers had less anxiety about starting OIT after having had peanut exposure through EPIT. Most children who transitioned from EPIT to OIT had no or minor symptoms initially, with symptoms lessening later in OIT. Most were also able to maintain or increase their peanut dose over time, achieving maintenance doses of 60–2,000 mg. Discussion In comparison with current literature on OIT for PA in children, the reported symptoms appeared less severe and less prevalent in the EPIT to OIT group. However, there were 3 participants who withdrew from OIT due to the development of intolerable symptoms. This study provides initial data in support of EPIT to OIT, and larger randomized controlled trials assessing effectiveness of the two therapies together are warranted.